European survey on general practitioners' perceptions on opportunistic single time point screening for atrial fibrillation. (19th May 2022) - Vermunicht, P; Engler, D; Schnabel, R B; Desteghe, L; Heidbuchel, H
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): This study falls within the AFFECT-EU project, which has received funding from the European Union's Horizon 2020 research and innovation Programme under grant agreement No 847770. Background: Opportunistic screening for atrial fibrillation (AF) by pulse taking or electrocardiogram (ECG) rhythm strip is recommended by the European Society of Cardiology (ESC) in all patients ≥65 years. Systematic ECG screening should be considered to detect AF in individuals above 75 years, or those at high risk of stroke. There is no clear guidance on how to implement opportunistic or systematic AF screening in daily clinical practice. Purpose: This study evaluated the perception of general practitioners (GPs) in Europe concerning value and practicalities to implement AF screening in daily clinical practice, focussing on opportunistic single time point screening. Methods: A descriptive cross-sectional study was conducted with a survey developed to assess (1) the overall perception concerning AF screening, (2) feasibility of opportunistic single lead ECG screening and (3) implementation requirements and barriers. This questionnaire was validated for its content during various iterations by experts in the field. The dissemination of the survey aimed to reach mainly GPs and was carried out through contacting GP organizations and personal GP networks. Results presented here were collected between July and mid-December 2021. Results: A total of 414 responses were collected (45.0% Eastern, 21.3% Central, 15.0% Northern, 12.8% Western, 5.3% Southern Europe and 0.7% outside Europe). The need for standardised AF screening was rated as 83.2 on a scale from 0 to 100, which was almost as high as for colon (85.6), breast (86.1) and cervical (89.2) cancers. The vast majority (88.6%) indicated that no AF screening programme is established in their region, and three out of four GPs (72.7%, lowest in Eastern and Southern Europe) were equipped with a 12-lead ECG, while a single lead ECG was less common (16.2%, highest in West Europe). Nevertheless, three in five GPs (59.2%) stated that they would feel confident in ruling out AF on a 30-second single lead ECG rhythm strip. To improve their confidence, 31.2% of GPs indicated that more education on ECG in general would be helpful, 25.7% would consider a standardised follow-up pathway with the possibility of a quick referral to the cardiologist of added value, and 22.4% would perceive a tele-healthcare service with advice on ECG tracings as helpful. The main obstacles reported by GPs to implement opportunistic single lead ECG screening were diverse (Figure 1) and several strategies were proposed to overcome these barriers (Figure 2). Conclusions: Despite the absence of a standardised AF screening programme, there is a strong perceived need for an evidenced based approach. To implement AF screening in clinical practice, integration with other healthcare programmes and software systems with algorithms to identify patients suitable for screening would be helpful.